Investigating the presence of different bottlenose dolphin ecotypes in the Mediterranean Sea - Michela Bellingeri; Alice Nebuloni; Gabriella La Manna; Aylin Akkaya; Jessica Alessi; Antonella Arcangeli; Davide Ascheri; Tim Awbery; Georges Azzinari; Caroline Azzinari; Marta Azzolin; Micaela Bacchetta; et al. (Scientific Reports, 2025)
Abstract The common bottlenose dolphin is a cosmopolitan species that can be found worldwide in all oceans except polar and sub-polar waters. This wide distribution is associated with a certain level of morphological variation, which seems consistent with the presence of a globally distributed pelagic/offshore ecotype and several coastal/inshore ecotypes distributed along the continental shelf. In the Mediterranean Sea, the common bottlenose dolphin is a regularly occurring species and the second most sighted cetacean after the striped dolphin. According to some studies, the Mediterranean bottlenose dolphin is more closely related to the Atlantic coastal ecotype, while others suggest a closer link with the pelagic ecotype. This apparent contradiction could stem from the coexistence of two ecotypes also within the Mediterranean Sea, as suggested by genetic analyses. We analysed data collected from 2004 to 2019 by 43 different research groups, distributed in different areas of the basin, and shared on the web-based GIS platform Intercet. We analysed the distribution and movements of 4919 bottlenose dolphins, individually identified through their natural dorsal fin markings, in relation to bathymetry and in particular to the 200-meter isobath that marks the edge of the continental shelf. In addition, we reconstructed the associations between individuals within connectivity networks, to identify possible segregations between ecotypes. Our results show that most bottlenose dolphin geographical units find their habitat over the continental shelf, while the analysed data do not support the coexistence of different ecotypes (pelagic vs. coastal) living in parapatry, as described in the adjacent waters of the eastern Atlantic Ocean.